The Relationship Between Body Awareness and Pain Severity, Static Balance, and Functional Performance in Female Patients with Knee Osteoarthritis: A Cross-Sectional Study - Beydaği, Muharrem Gökhan; Bozgeyik-Bağdatli, Sibel; Kisacik, Pınar; Apaydin, Hakan; Topuz, Semra; Erden, Zafer (AVES, 2026)
Objectives: To examine the associations between body awareness (BA) and pain, static balance, and functional performance in women with knee osteoarthritis (OA). Methods: This cross-sectional study included 24 women with moderate unilateral knee osteoarthritis (mean age 55.5 ± 7.5 years; body mass index (BMI) 29.9 ± 4.9 kg/m^2). Body awareness (Body Awareness Questionnaire, BAQ), pain during activity (visual analogue scale, VAS), static balance (anteroposterior/mediolateral postural sway during eyes-open and eyes-closed stance using a force plate), and functional performance (Timed Up & Go, TUG) were assessed. Spearman correlations were calculated. Hierarchical multiple regression tested whether BAQ independently predicted pain and anteroposterior (AP) sway after adjusting for age, BMI, and disease duration. Results: Body Awareness Questionnaire was negatively correlated with disease duration (r = -0.680, P < .001), VAS (r = -0.654, P < .001), and eyes-closed AP sway (r = -0.738, P < .001), and moderately correlated with eyes-open AP sway (r = -0.456, P = .025). Body Awareness Questionnaire was not associated with mediolateral sway or TUG (P > .05). In adjusted regression models, BAQ was not a statistically significant independent predictor of pain or AP sway (all P > .05). Conclusion: Higher BA was associated with lower pain and reduced AP sway in bivariate analyses, but these relationships attenuated after accounting for age, BMI, and disease duration. Longitudinal studies with larger samples and more sensitive functional measures are warranted. Content of this journal is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.
Keywords: Body awareness; functional performance; knee osteoarthritis; pain; static balance